PENGARUH EMOSI, MATERIALISME, LITERASI KEUANGAN, PERSEPSI RISIKO DAN PENGALAMAN KEUANGAN TERHADAP PROPENSITY TO INDEBTEDNESS (STUDI PADA NASABAH KREDIT PLUS KENDARI) - Lucia Evianti Patulak; Buyung Sarita; Wahyuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The research was conducted with the aim of analyzing the influence of emotions, materialism, financial literacy, risk perception and financial experience on propensity to indebtedness. Primary data was obtained through distributing 100 questionnaires to Kredit Plus Kendari customers then processed with the SPSS 25.0 software application. The results of the research that have been done state that there is an effect of emotion, financial literacy and experience on propensity to indebtedness which has a negative significant effect, the effect of materialism on propensity to indebtedness has a positive significant effect, while the risk perception of propensity to indebtedness has no significant effect.